Complete submergence triggers synergistic regulation of gibberellin-abscisic acid balance and pith cavity development to promote stem elongation in Alternanthera philoxeroides - Jing, Shufang; Liu, Hongwei; Li, Yuezhen; Bai, Zhenxia; Yu, Mingfu; Liu, Junhe; Li, Dahong (Frontiers in Plant Science, 2025)
Submergence, a major abiotic stress in hydrologically dynamic ecosystems, poses severe challenges to plant survival and growth. Existing studies have demonstrated that plants employ a suite of adaptive strategies to tolerate submergence. These divergent adaptive responses are endogenously regulated by phytohormones; yet, the underlying mechanisms that connect hormonal regulation, anatomical plasticity, and growth adaptation in the context of submergence remain insufficiently elucidated. Alternanthera philoxeroides (Mart.) Griseb. is widely distributed in disturbed, flood-prone habitats and exhibits exceptional adaptability to hydrological fluctuations, making it a suitable species for exploring submergence stress responses. This study investigated A. philoxeroides’ responses to three hydrological conditions (non-submergence, partial submergence, complete submergence), focusing on stem growth and its anatomical and hormonal regulatory drivers. Results revealed an unexpected growth pattern: complete submergence induced significantly faster stem elongation than partial submergence, with this growth-promoting effect most pronounced in immature stems—particularly the basal parts of immature internodes. This elongation correlated positively with enlarged pith cavities and elevated gibberellin (GA4), while it was significantly negatively correlated with abscisic acid (ABA). GA4 content and pith cavity area were also highly positively correlated. These findings unravel a critical adaptation mechanism in A. philoxeroides: coordinated hormonal adjustments (GA4 up, ABA down, higher GA4/ABA) and morphological remodeling (pith cavity enlargement) that synergistically support enhanced growth under severe submergence. This work advances understanding of plant adaptive strategies under climate-driven hydrological stress, enriches insights into abiotic stress response mechanisms, and provides valuable references for wetland ecosystem conservation and the improvement of crop submergence tolerance.